Bingo Games in students’ vocabulary and reading comprehension - Qomariyah, Siti Syafi’atul; Utama, I Made Permadi (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2020)
The aim of the present study is to explore the effect of using Bingo Games on students’ vocabulary and reading comprehension. The subjects of the study were tenth-grade students of SMAN 8 Mataram. The researchers used experimental design by applying random sampling technique. The researchers used two group classes, namely X MIA 1 as experimental and X MIA II as control class. In collecting the data, vocabulary and reading test were used as an instrument. The data was analyzed used descriptive and inferential statistics. The result revealed that there were significant improvement on the students’ posttest. It proves that Bingo games was one of alternative strategy that can be applying in teaching vocabulary and reading comprehension.  DOI: 10.26905/enjourme.v5i2.5056